Automated Representation of Style by Feature Space Archetypes: Distinguishing Spatial Styles from Generative Rules - Hanna, Sean (International journal of architectural computing, 2007)
Style is a broad term that could potentially refer to any features of a work, as well as a fluid concept that is subject to change and disagreement, yet approaches to representing it too often seek either a pre-defined set of generative rules or list of measurable features. Instead, a general and flexible method of retrospectively and automatically representing style is proposed based on the idea of an archetype, to which real designs can be compared, and tested with examples of architectural plans. Unlike a fixed, symbolic representation, both the measurements of features that define a style and the selection of those features themselves can be performed by the machine, making it able to generalise a definition automatically from a set of examples. This process is implemented in analysis, and coupled with a generative algorithm to produce plans in a learned style.